Pour une correction phonétique personnalisée en FLE ou de la remédiation « sur mesure » « - Dańko, Magdalena; Hamm, Dominique (Studia Romanica Posnaniensia, 2017)
Herein we would like to rise up a concern of the error correction of pronunciation in French as a Foreign Language. The results of the experimental acoustic analysis (concerning the values of acoustic vowel formants F1 and F2) enabled to precisely specify the difficulties of the experiment’s participants in a field of French vocal system. In relation to the differences of vocal systems of French and Polish language we suggest custom solutions on a didactic level. Based on verbo-tonal method for phonetic integration the error correction activities had been individually elaborated for each participant.